Developing a tool to measure and monitor carbon storage for use in planning green spaces in urban areas the case of Antipolo City proper - Dumaligan, Faith T. (School of Urban and Regional Planning, University of the Philippines Diliman, 2017)
The local practice of planning urban open spaces is generally geared towards allocating open spaces in terms of quality. In a decade where the natural phenomenon is being intensified by effects of anthropogenic climate change. Its is important to plan open spaces not solely in terms of land area coverage but essentially in terms of ecosystem function. Furthermore, as studies have correlated urbanization as a driver of anthropogenic climate change effects, it is strategic for urbanizing countries such as the Philippines, to plan urban open spaces as a climate change mitigation strategy, particularly, in terms of its function, as a carbon sink. This study proposes developing a tool to measure and monitor carbon storage for use in planning green spaces in urban areas. The development of the tool is an offshoot of a carbon storage assessment done in a study in 2014 (Yap et al. 2014) using estimation factors. Devised to have both urban green space carbon storage assessment and management procedures, the tool provides results that can be the bases of preserving and allotting open spaces during the conduct of actual local planning activities. different public urban open spaces in Antipolo City were used as case studies in developing the tool. Theses were the Town Plaza, the Antipolo Church Grounds, the City proper Public Streetscape, and the Rizal Provincial Capitol and Ynares Center Complex. The Hinulugang Taktak National Park was included as part of the study are per instructions from the City Planning and development Office. The concept of net primary productivity is the scientific basis of developing the carbon storage assessment aspect of the tool, as it is an indicator of carbon storage growth in an ecosystem within a period of time. Photosynthesis, on the other hand, formed the basis for developing the carbon storage management feature of the tool as it represents the natural process concerning movement of carbon from the atmosphere to terrestrial storage such as vegetation and soil through light, water, presence of carbon dioxide, and soil nutrients. The urban green space carbon storage assessed by the tool are trees, palms and soil. Carbon emissions from soil and plant respiration and urban green space maintenance activities have also been accounted and subtracted from the amount of total carbon storage from soil. trees and palms. Through the carbon storage assessment too, the study was able to compute for the carbon sink for Years 2014 and 2017 for each public urban open space in the study. Despite various methods used in data collection, the results were able to provide a better carbon storage estimation compared to the assessment using estimation factors. Through the carbon storage management tool, the study was able to identify spatial factors that affect tree and palm carbon storage capacities. Statistical analyses revealed that the physical factors that were derived from biogeochemical factors of photosynthesis have significant relationships with tree and palm carbon storage. From the results of both the assessment and management tools, the study was able to propose examples of urban green space redevelopment plans to augment the carbon storage capacities of public urban open spaces that are largely composed of paved surface areas rather than green spaces. Furthermore, the tool served as a basis fro recommending guidelines in planning urban open space as carbon sinks based on spatial factors that greatly impact on carbon storage.